Investigating problem-solving process of pre-service mathematics teachers who are truth-seekers. (March 2019) - Kurniati, D; Purwanto; As'ari, A R; Dwiyana
Abstract: The present research aims to investigate the problem-solving process of pre-service Mathematics teachers who are truth-seekers. The process of problem-solving is the stages in solving two types of problems, namely the problems with contradictory information and problems with no universal set. The participants are four Mathematics education students in the University of Jember who perform truth-seeking. The research stages comprised of (1) giving four problems and recording the participant's behavior during solving the problems, (2) analyzing the answer sheets and recordings, (3) doing triangulation through interviews, and (4) summarizing the tendency of the problem-solving process of pre-service mathematics teachers who are truth-seekers. The results of this research are (1) when solving the problems with contradictory information, participants tend not to proceed to the process of determining the solution of the p roblem, and (2) when solving the problems with no universal set is given, participants tend to determine the universal set before solving the problems. Therefore, the trends of the solving-problem process of the pre-service Mathematics teachers who are truth-seekers are not to determine the solution if the problems have wrong information and will add the universal set if the informations in the problems have not the universal set.